Two Pillars of Character Education: Harmony of Extracurricular Activities and School Culture - Fajar Nur Cahyani; Marzuki; Puspa Widyastuti (Universitas Pendidikan Ganesha, 2025)
Character education requires an approach that can instill values deeply through habituation, role modeling, and real-life experiences, rather than through theory alone. This study aims to analyze the role of extracurricular activities and school culture as two main pillars in shaping student character. The research employed a qualitative approach using a literature study method. Data were collected from primary sources, including empirical research, secondary sources such as books and educational policy documents, and supporting sources from reliable media articles. Research instruments included a literature criteria checklist and a findings recording sheet, validated through expert review. Data analysis was conducted qualitatively through identification of main themes, concept classification, interpretation of relationships among concepts, and synthesis to achieve a comprehensive understanding. The results indicate that extracurricular activities such as Scouting, Red Cross Youth (PMR), and arts programs are effective in fostering responsibility, leadership, cooperation, and self-confidence through direct involvement. School culture contributes to shaping character systemically through habituation, teacher role modeling, and an environment that supports discipline, religiosity, and social concern. The study concludes that the integration of extracurricular activities and school culture synergistically is more effective in developing student character than implementing them separately. The implications emphasize the need for schools to design an integrated character education strategy by aligning extracurricular activities with school culture, thereby creating a sustainable and practical model of character formation applicable in broader educational contexts.